Combining theory and usability testing to inform optimization and implementation of an online primary care depression management tool - Nicola McCleary; Justin Presseau; Isabelle Perkins; Brittany Mutsaers; Claire E. Kendall; Janet Yamada; Katharine Gillis; Douglas Green (BMC Medical Informatics and Decision Making)
Abstract Background The ‘Ottawa Depression Algorithm’ is an evidence-based online tool developed to support primary care professionals care for adults with depression. Uptake of such tools require provider behaviour change. Identifying issues which may impact use of an innovation in routine practice (i.e. barriers to and enablers of behaviour change) informs the selection of implementation strategies that can be deployed with the tool to support use. However, established theory-informed barriers/enablers assessment methods may be less well suited to identifying issues with tool usability. User testing methods can help to determine whether the tool itself is optimally designed. We aimed to integrate these two methodological approaches to i) identify issues impacting the usability of algorithm; and ii) identify barriers to and enablers of algorithm use in routine practice. Methods We conducted semi-structured interviews with primary care professionals in Ottawa, Canada. To evaluate usability, participants used a written patient scenario to work through the algorithm while verbalizing their thoughts (‘Think Aloud’). Participants were then asked about factors influencing algorithm use in routine practice (informed by the Theoretical Domains Framework). We used the codebook approach to thematic analysis to assign statements to pre-specified codes and develop themes pertaining to usability and routine use. Results We interviewed 20 professionals from seven practices. Usability issues were summarised within five themes: Optimizing content and flow to align with issues faced in practice, Enhancing the most useful algorithm components, Interactivity of the algorithm and embedded tools, Clarity of presence, purpose, or function of components, and Navigational challenges and functionality of links. Barriers to and enablers of routine use were summarised within five themes: Getting to know the algorithm, Alignment with roles and pathways of influence, Integration with current ways of working, Contexts for use, and Anticipated benefits and concerns about patient communication. Conclusions Whilst the Ottawa Depression Algorithm was viewed as a useful tool, specific usability issues and barriers to use were identified. Supplementing a theory-based barriers/enablers assessment with usability testing provided enhanced insights to inform optimization and implementation of this clinical tool. We have provided a methods guide for others who may wish to apply this approach.